2019
DOI: 10.11646/phytotaxa.391.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Hermatomyces trangensis sp. nov., a new dematiaceous hyphomycete (Hermatomycetaceae, Pleosporales) on sugar palm in Thailand

Abstract: A new species of a hyphomycetous fungus, Hermatomyces trangensis, was collected during an investigation of the diversity of palm fungi in Na Yong district, Trang province, Southern Thailand, and is introduced in this paper based on morphological and molecular evidence. The fungus is characterized by the production of only one type of conidia, globose or subglobose in front view, broadly ellipsoidal or oblong in lateral view, with dark brown to black central cells and subhyaline to pale brown peripheral cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…The ITS1 showed 99.73% homology with that of the L. chartarum strain with the GeneBank Accession No.KM877491.1, and the ITS4 sequence was found to possess 100% homology with that of the L. chartarum strain KNU14-16 (GenBank Accession No. KP055597.1) ( Figure 1) [23]. Our results from the phylogenetic tree analysis supported these alignment results.…”
Section: Fungal Isolation and Identificationsupporting
confidence: 80%
See 4 more Smart Citations
“…The ITS1 showed 99.73% homology with that of the L. chartarum strain with the GeneBank Accession No.KM877491.1, and the ITS4 sequence was found to possess 100% homology with that of the L. chartarum strain KNU14-16 (GenBank Accession No. KP055597.1) ( Figure 1) [23]. Our results from the phylogenetic tree analysis supported these alignment results.…”
Section: Fungal Isolation and Identificationsupporting
confidence: 80%
“…For example, the phylogenomic investigation of the ITS1 sequence demonstrated that the strain was C. trifolii. In our analysis, the phylogenetic relationships based on ITS1 also showed that the L. chartarum strain had a high bootstrap value of 99% ( Figure 1) [23].…”
Section: Fungal Isolation and Identificationmentioning
confidence: 53%
See 3 more Smart Citations